Kemampuan Ibu dalam Penanganan Pertama Kejang Demam - Antik Wijayanti; Agus Khoirul Anam; Andi Hayyun Abiddin (Universitas Malahayati Lampung, 2025)
ABSTRACT Improper and rapid handling of febrile seizures can cause complications and can lead to death. The mother's ability in first aid for febrile seizures is essential so that if a child has a febrile seizure, the parents can cope. The purpose of this study was to identify the mother's ability regarding first aid for febrile seizures in children before being taken to the hospital. This study used a quantitative method with a quasi-experimental design through a one-group pre-test post-test design approach with a sample of 30 respondents, taken using a purposive sampling technique from the toddler posyandu in Gondang Village, Nganjuk. Data collection used questionnaires and observations of the mother's ability—the data analysis technique in descriptive statistics by calculating the percentage. The results of the study obtained 43% of respondents' knowledge in the poor category, and 30% of respondents' abilities in the sufficient category. Based on the study above, it can be concluded that the mother's knowledge in the poor category was 13 respondents (43%) based on the lack of exposure to information. Lack of knowledge can result in errors in implementation and can endanger children. The mother's ability in the good category was 13 respondents (43%), sufficient as many as 10 respondents (33%), and lacking as many as 7 respondents (23%). This is based on the level of knowledge and age factors that influence the mother's ability to provide initial treatment for febrile seizures. Keywords: Febrile Seizures, Mother, First Handling Of Febrile Seizures ABSTRAK Penanganan kejang demam yang tidak tepat dan cepat dapat menimbulkan komplikasi dan dapat menyebabkan kematian. Kemampuan ibu dalam penanganan pertama kejang demam sangat penting sehingga apabila terjadi kejang demam pada anak, orang tua mampu mengatasi. Tujuan penelitian ini untuk mengidentifikasi kemampuan ibu mengenai penanganan pertama kejang demam pada anak sebelum dibawa ke rumah sakit. Penelitian ini menggunakan metode kuantitatif dengan design quasi experimental melalui pendekatan one grup pre-test post-test design dengan sampel sebanyak 30 responden, diambil dengan teknik purposive sampling dari posyandu balita desa gondang, Nganjuk. Pengumpulan data menggunakan kuisioner dan observasi kemampuan ibu. Teknik Analisa data dalam statistik deskriptif dengan melakukan perhitungan presentase. Hasil penelitian diperoleh 43% pengetahuan responden kategori kurang, dan 30% kemampuan responden kategori cukup. Berdasarkan penelitian diatas dapat disimpulkan pengetahuan ibu dalam dalam kategori kurang sebanyak 13 responden (43%) hal ini didasari dengan kurangnya terpapar informasi. Kurangnya pengetahuan dapat mengakibatkan kesalahan dalam pelaksanaan dan dapat membahayakan anak. Kemampuan ibu dalam kategori baik sebanyak 13 responden (43%), cukup sebanyak 10 responden (33%), dan kurang sebanyak 7 responden (23%). Hal ini didasari dengan adanya tingkat pengetahuan dan faktor usia yang mempengaruhi kemampuan ibu dalam penanganan pertama kejang demam. Kata Kunci: Anak, Kejang Demam, Ibu, Penanganan Pertama Kejang Demam